Risk Factors for the Presence of Campylobacter Sp. in Lithuanian Broiler Flocks - Pieskus, Juozas; Butrimaite-Ambrazeviciene , Ceslova; Kazeniauskas, Edvardas; Stanevicius, Zenonas; Mauricas, Mykolas (International Journal of Poultry Science, 2008)
The objective of this study was to define the incidence of Campylobacter in Lithuanian broiler flocks. The incidence of both Campylobacter and Salmonella and the seasonal fluctuations on the occurrence of pathogens were focused in this study. Faeces, dust and water samples were obtained at the farms 1-2 days before the broiler slaughtering. The cecum was removed after slaughtering. Microbiological study of the faeces and cecum content showed, that 18.4% (95% CI 7.0-29.0) of flocks were colonized with Campylobacter sp. However, dust and water samples were found to be free of Campylobacter. The study of influence of other pathogens (Salmonella) on the prevalence of Campylobacter sp. showed, that 12.2% (95% CI 3.0-21.0) of broiler flocks were colonized with both pathogens (Campylobacter and Salmonella). Campylobacter jejuni was predominant among the Campylobacter-positive flocks. The majority of broiler flocks harbored Campylobacter in spring (30.7%).